TREND OF INTERNET USAGE AND LEARNING STYLE OF DIGITAL NATIVES - Lai, Yin Ling; Lee, Joseph (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The use of internet has become a way of living since its inception in the 80s. With the advancement of informatics technologies, it has also created an unprecedented pressure to the education sector in keeping up with the pace of change in societal needs and technological innovations. It is with the aim of facilitating better learning outcomes attainment at tertiary education level among the digital natives, this study is set to find out how frequently technology savvy students use the internet and what the key internet activities are. The findings are subsequently analyzed to establish a correlation between the frequencies of internet usage and preferred learning style. It is observed that the primary internet usage of 784 respondents is in entertainment and communication in their daily internet routine. However, the association of the internet with the preferred learning style is inconclusive.